Giải các phương tình sau:
a) \(x^3-3x^2+12x-5=2\sqrt{5x-1}+\sqrt[3]{3x-2}\)
b) \(4x^2+24x+17=2\sqrt{2x+5}+\sqrt[3]{4x+10}\)
c) \(2x^3-5x^2+16x-3=2\sqrt[3]{4x-1}+\sqrt[3]{2x+7}\)
d) \(2x^2+11x+12=2\sqrt{2x+3}+\sqrt[3]{x+2}\)
e) \(2x^2+3x-3-2\sqrt{2x+1}-\sqrt[3]{4x+2}=0\)
Giải các phương trình
a) \(\sqrt{2x+9}=\sqrt{5-4x}\)
b) \(\sqrt{2x-1}=\sqrt{x-1}\)
c) \(\sqrt{x^2+3x+1}=\sqrt{x+1}\)
d) \(\sqrt{2x^2-3}=\sqrt{4x-3}\)
a)\(\sqrt{x^2+2x+10}+x^2+2x+8=0\)
b)\(15x-2x^2-5=\sqrt{2x^2-15x+11}\)
c)\(\sqrt{9x^2+45}+\sqrt{16x^2+80}+3\sqrt{\frac{x^2+5}{16}}-\frac{1}{4}\sqrt{\frac{25x^2+15}{9}}=9\)
d)\(3x^2+21x+18+2\sqrt{x^2+7x+7}=2\)
e)\(\sqrt{x^2+3x+2}-2\sqrt{2x^2+6x+2}=-\sqrt{2}\)
f)\(\sqrt{x-1}+\sqrt{x+3}-\sqrt{x^2+2x-3}-1=0\)
\(6x^2+2x+\sqrt[3]{3x^2+x+4}-10=0\)
\(x+1+\sqrt{x^24x+1}=3\sqrt{x}\)
\(x^2+2x\sqrt{x^2+4x+1}=3\sqrt{x}\)
\(\sqrt{x+8}+\dfrac{9x}{\sqrt{x+8}}-6\sqrt{x}=0\)
Giải các phương trình sau:
a) \(x^3-x^2+2x=\sqrt{2x-1}+\sqrt{4x-3}\)
b) \(x^3-x^2+3x+13=4\left(\sqrt{x+3}+\sqrt{3x+1}\right)\)
c) \(x^3-4x^2+6x-1=\sqrt{2x-3}+2\sqrt{x-1}\)
d) \(x^3+4x^2+9x+9=2\sqrt{3x+4}+\sqrt{2x+3}\)
e) \(2x^2-4x+11=2\sqrt{3x-5}+3\sqrt{2x+5}\)
Giải các phương trình sau:
a) \(x^3-x^2+2x=\sqrt{2x-1}+\sqrt{4x-3}\)
b) \(x^3-x^2+3x+13=4\left(\sqrt{x+3}+\sqrt{3x+1}\right)\)
c) \(x^3-4x^2+6x-1=\sqrt{2x-3}+2\sqrt{x-1}\)
d) \(x^3+4x^2+9x+9=2\sqrt{3x+4}+\sqrt{2x+3}\)
e) \(2x^2-4x+11=2\sqrt{3x-5}+3\sqrt{2x+5}\)
1.a) Rút gọn: \(\frac{2x+\sqrt{x}-1}{1-x}+\frac{2x\sqrt{x}+x-\sqrt{x}}{1+x\sqrt{x}}\)
b) \(\sqrt[3]{3+\sqrt{17}}+\sqrt[3]{3-\sqrt{17}}\)
2. Giải phương trình:
a) \(\sqrt{x^2-3x+2}+\sqrt{x+3}=\sqrt{x-2}+\sqrt{x^2+2x-3}\)
b) \(\sqrt{2x^2-9x+4}+3\sqrt{2x-1}=\sqrt{2x^2+21x-11}\)
c) \(x^2+2015x-2014=2\sqrt{2017x-2016}\)
d) \(\sqrt{\left(1+x^2\right)^3}-4x^3=1-3x^4\)
\(\sqrt{2x^2-1}+\sqrt{x^2-3x-2}=\sqrt{2x^2+2x+3}+\sqrt{x^2-x+2}\)
Giải pt:
a) \(\sqrt{2x^2-3}\)=\(\sqrt{4x-3}\)
b) \(\sqrt{2x-1}\)=\(\sqrt{x-1}\)
c) \(\sqrt{x^2-x-6}\)=\(\sqrt{x-3}\)
d) \(\sqrt{x^2-x}\)=\(\sqrt{3x-5}\)
Giúp em với, anh thịnh giúp em xíu á